The Effectiveness of Cadre Training in Interpreting Toddler Nutritional Status using Anthropometric Indicators - Fithri, Hanifa Amalia; Budiastutik, Indah; Saleh, Ismael; Marlenywati, Marlenywati; Permata, Widya (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Anthropometric knowledge is important for assessing nutritional status; however, measurement errors can affect data quality. Therefore, it is necessary to improve the capacity of the cadres to increase the accuracy of the nutritional data. This study aimed to determine the effectiveness of cadre training in improving their ability to interpret the nutritional status of toddlers using anthropometric indicators.Methods: This study used a quantitative research methodology with a quasi-experimental, one-group, pretest-posttest design. The training methods used were equipment preparation, presentation of nutrition and anthropometry theory, discussion, demonstration, and measurement practice by trainers. The training research subjects were 39 posyandu cadres selected through purposive sampling method. Data analysis was performed using a paired t-test.Results: The cadres were mostly in the age group of 31-40 years, housewives, and more than half of them were in junior high school level and below. The training model improved the cadres’ knowledge in the interpretation of the anthropometric measurement results from a score of 4.79 to 6.74 after the training, with p=0.0001, indicating a significant improvement.Conclusion: Cadre training significantly improved the ability to interpret toddlers’ nutritional status based on anthropometric indicators, supporting more accurate growth monitoring and early detection of nutritional problems at the community level.